2016
DOI: 10.1002/adma.201602787
|View full text |Cite
|
Sign up to set email alerts
|

Giant Negative Electrocaloric Effects of Hf0.5Zr0.5O2 Thin Films

Abstract: Hafnia (HfO )-zirconia (ZrO ) solid solution films show giant positive (ΔT = 13.4 K) and negative (ΔT = -10.8 K) electrocaloric effects that can be simply controlled by tuning the Hf/Zr ratio. It is expected that the combination of the electrocaloric effects with opposite signs in this lead-free, simple, binary oxide can significantly improve the efficiency of electrocaloric cooling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
68
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(73 citation statements)
references
References 42 publications
3
68
0
2
Order By: Relevance
“…However, compared with the great progress made in positive EC effect such as T ~ 45.3 in Pb0.8Ba0.2ZrO3 AFE/FE coexisted thin film (~ 320 nm thickness) and T ~ 53.8 K in Pb0.97La0.02(Zr0.75Sn0.18Ti0.07)O3 AFE thick film (~ 2 m thickness), [6,7] the progress made in negative EC effect has still remained at a relatively low level such as T ~ − 5.76 K in Pb0.97La0.02(Zr0.95Ti0.05)O3 AFE thin film (650 nm thickness), [10] T ~ − 6.62 K in Pb0.96Eu0.04ZrO3 AFE thin film (550 nm thickness) and T ~ − 10.8 K in Hf0.5Zr0.5O2 FE thin film (9.2 nm thickness). [11,12] In contrast to the extensive research on the positive EC effect, less attention has been paid to the negative EC effect due to its elusive physical mechanism. Based on previous research work, the origin of the negative EC effective may be ascribed to some factors such as the non-collinearity between the electric field and the polarization (dipole & defect dipole).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, compared with the great progress made in positive EC effect such as T ~ 45.3 in Pb0.8Ba0.2ZrO3 AFE/FE coexisted thin film (~ 320 nm thickness) and T ~ 53.8 K in Pb0.97La0.02(Zr0.75Sn0.18Ti0.07)O3 AFE thick film (~ 2 m thickness), [6,7] the progress made in negative EC effect has still remained at a relatively low level such as T ~ − 5.76 K in Pb0.97La0.02(Zr0.95Ti0.05)O3 AFE thin film (650 nm thickness), [10] T ~ − 6.62 K in Pb0.96Eu0.04ZrO3 AFE thin film (550 nm thickness) and T ~ − 10.8 K in Hf0.5Zr0.5O2 FE thin film (9.2 nm thickness). [11,12] In contrast to the extensive research on the positive EC effect, less attention has been paid to the negative EC effect due to its elusive physical mechanism. Based on previous research work, the origin of the negative EC effective may be ascribed to some factors such as the non-collinearity between the electric field and the polarization (dipole & defect dipole).…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous research work, the origin of the negative EC effective may be ascribed to some factors such as the non-collinearity between the electric field and the polarization (dipole & defect dipole). [10,[12][13][14][15][16][17] In general, the largest negative EC effect appears not at the largest applied electric field but at a moderate one, under which the largest degree of non-collinearity yields the maximum T & S. [10,11] Therefore, increasing the possible maximum applied electric field by improving the dielectric breakdown strength of the materials, which is normally regarded as one of effective methods to enhance the positive EC effect, might not be a valid method to enhance the negative EC effect. Chemical element doping is usually chosen to be a simple and effective method to improve the performance of materials.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the large ΔT values obtained in the positive EC effect, the absolute value of the ΔT observed in negative EC effect is smaller, such as ΔT~-5.76 K at 59°C and 338 kVcm -1 in Pb0.97La0.02(Zr0.95Ti0.05)O3 thin film (650 nm thickness) [15], ΔT~-6.62 K at 130°C and 709 kVcm -1 in Pb0.96Eu0.04ZrO3 thin film (550 nm thickness) [16], and ΔT~-10.8 K at 175°C and 3260 kVcm -1 in Hf0.5Zr0.5O2 thin film (9.2 nm thickness) [17], etc. Usually, the origin of a negative EC effect can be traced to the non-collinearity between the electric field and the polarization [15,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Li et al suggested that the 180°d omain structure of PbTiO3 can be utilized as a combined nano-laminate structure to include positive and negative EC materials [22]. As a result, the combination of positive and negative EC effects in thin films can complete the cooling process in one step with a sustained applied electric field in the cooling process [17,23], leading to a high cooling efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In order to get better ECE, most of the scholars put their focus on thin films that can bear greater electric field. For example, the negative ECE was reported in a La-doped Pb(Zr,Ti)O 3 film [11], in Hf 0.5 Zr 0.5 O 2 thin films [12] and in Eu-doped AFE PbZrO 3 thin films [13]. Thin films have the advantage on the application in small solid-state cooling devices, but the bulk materials are essential to the middle-and large-scale devices, such as refrigeration [14,15].…”
mentioning
confidence: 99%